Das vidas que não (se) contam: dispositivos de desinstitucionalização da medida de segurança no Pará - Silva, Alyne Alvarez (2015)
In Brazil, people diagnosed with mental disorder are now considered subjects of rights from the Psychiatric Reform Law. The same can not be said if these same people come into conflict with the law. Understood as dangerous, they are throw out of the legal system aligned with human rights due to a supposed intellectual and volitional disability in the face of criminal act. The periculosity attested by forensic experts authorizes the justice to consider them in an inimputability situation, what, besides to not allow them to be called to answer for their acts, motivates the restriction of a number of constitutional rights. Considering the reality of rape and extreme violence own this context, this research aimed to discuss the processes of institutionalization and deinstitutionalization of so-called "insane offenders" in State of Pará, using the cartography method as intervention-research. We mapped some of the lines that establish the device "security measure" and the processes of institutionalization promoted by it, considering the production of fear as governmentality strategy in the constitution of punitive subjectivities. At the same time, we follow the flows triggered by the research towards the deinstitutionalization processes of this population. From the Custodial Psychiatric Hospital Santa Isabel of Pará, we have described the practices of power-knowledgesubjectivation intended for institutionalized people and profiled those submitted to security measure, these lives which have never been counted. In addition, it have been built devices - such as art workshops to psychiatric patients, itinerant exhibition of the resulting works, conversation circles with workers in the mental health network and a documentary film - favoring the connection of actors and various elements to function as machines that make see and talk about security measure dispositive, composing new sensibilities and forging aesthetic vectors of deinstitutionalization. The co-organization of a Meeting among various actors of justice and the rule of executive managers still allowed us following the configuration of a program of deinstitutionalization and approached the legal-political dimension of the Psychiatric Reform when we have discussed the person's responsabilization model with disorder mental in conflict with the law